Immunomodulatory Effect Of Withania Somnifera (Ashwagandha) Against Fenvalerate Induced Immunotoxicity - P.AMARAVATHI,; CH.SRILATHA,; V.RAMADEVI,; K.SUJATHA, (International Journal of Pharma and Bio Sciences, 2012)
Fenvalerate is a synthetic pyrethroid insecticide that has been in use since 1976 and commonly used in agriculture and other domestic applications due to its high insecticidal activity and low mammalian, avian and phytotoxicities. Withania somnifera (Ashwagandha) is medicinal plant that is having immunomodulatory activity. The present study was carried out by procuring 144 female rats and was randomly divided into eight groups consisting of 18 rats in each group. Fenvalerate (20% EC) gavaged per orally using ground nut oil as vehicle @ 42.5, 21.25 and 10.125 mg / kg b.wt. to groups II, III and IV respectively and ashwagandha @ 200 mg / kg b.wt. in distilled water was given along with Fenvalerate to group V, VI and VII for 6 weeks to study ameliorative effects. Group I and VIII kept as control for toxin and ashwagandha fed groups respectively. Six rats from each group were sacrificed at fortnight interval. HA and DNCB contact sensitivity test were performed to assess the immune response. Significant decrease in HA titers and DNCB dermal sensitivity was observed in all toxin fed groups and indicating decrease in cell mediated immunity and humoral immunity.